Confirmation that RIPK4 mutations cause not only Bartsocas‐Papas syndrome but also CHAND syndrome. Issue 11 (21st September 2017) - Busa, Tiffany; Jeraiby, Mohammed; Clémenson, Alix; Manouvrier, Sylvie; Granados, Viviana; Philip, Nicole; Touraine, Renaud
Abstract : CHAND syndrome is an autosomal recessive disorder characterized by curly hair, ankyloblepharon, and nail dysplasia. Only few patients were reported to date. A homozygous RIPK4 mutation was recently identified by homozygosity mapping and whole exome sequencing in three patients from an expanded consanguineous kindred with a clinical diagnosis of CHAND syndrome. RIPK4 was previously known to be implicated in Bartsocas‐Papas syndrome, the autosomal recessive form of popliteal pterygium syndrome. We report here two cases of RIPK4 homozygous mutations in a fetus with severe Bartsocas‐Papas syndrome and a patient with CHAND syndrome. The patient with CHAND syndrome harbored the same mutation as the one identified in the family previously reported. We thus confirm the implication of RIPK4 gene in CHAND syndrome in addition to Bartsocas‐Papas syndrome and discuss genotype/phenotype correlations.